Impact of Financial Literacy on the Socio-Economic Status of the Tharu Community in Nepal - Jaishi, Bishnu Prasad; Mahato, Bir Bahadur (Madhyabindu Journal, 2025)
Financial literacy plays a crucial role in achieving the Sustainable Development Goals (SDGs). This study examines how financial literacy affects social and economic status in Kawaoti-13, located in the Nawalparasi-East District of Nepal. We employed a cross-sectional and descriptive research design, selecting a sample of 384 households for the study. We gathered data using a survey questionnaire administered to the heads of each household. We analyzed the data using various statistical methods, including exploratory factor analysis and frequency distribution. Our findings reveal that financial literacy significantly enhances social and economic status. This outcome aligns with previous research and underscores the importance of financial knowledge in improving individual well-being and mobility. The study concludes that individuals who possess financial literacy can better meet their social and economic needs. These results highlight the necessity of promoting financial literacy to empower communities and contribute to sustainable development in Nepal.